Politics in France and Europe
XI, 272 p.
Keywords: This book offers an in-depth analysis of political life in France and Europe at the beginning of the 21st century at a time of change and crisis. Encompassing questions about values, political actors and electoral choices, it is dedicated particularly to scholars and students enrolled in comparative politics programs.